Optimasi transplantasi menggunakan sel donor dari ikan gurame muda dan ikan nila triploid sebagai resipien - Alimuddin .; M. Zairin Junior; Harton Arfah (Institut Pertanian Bogor, 2010)
Testicular cell transplantation technology can be used in fish seed production engineering. In this study, optimization of transplantation using donor cells from young gouramy and triploid tilapia (3N) as recipient. Triploid tilapia is produced using heat shock method. The testes of male gouramy (body weight of 400- 850 g) was dissociated using 0.5% trypsin. Dissociated testicular cells was injected into the peritoneal cavity of tilapia larvae. Analysis of donor cell colonization was carried out using PCR method with DNA template that had been extracted from the gonad of 2-month-old tilapia. PCR was performed using specific primers for the growth hormone gene and (3-actin as an internal control of DNA loading. The results of nucleoli preparation showed that the success of triploidyzation was 88.5%. The gonad size of diploid (2N) and 3N recipient were relatively similar, while in not transplanted 3N tilapia was rudimentary. PCR results showed that the transplanted 3N tilapia has a DNA band of the same size with gouramy, while in control was not. This indicated that donor cells have been colonized in the gonads of recipient. The donor cell colonization in recipient 3N (78%) was higher than that of 2N (50%). Further research is required to determine the ability of donor cells differentiate into sperm and eggs in recipient gonad.